Leadership and organizations - Henrique de Faria, José; Meneghetti, Francis Kanashiro (Revista de Psicologia, 2011)
Leadership can be considered a social role to be played with and support some basic principles. The leadership that seeks to follow these principles unleashes the human potential of individual member of a collective. Many people depend on the leader, who put their hopes in him to improve their working conditions and achieve their individual goals. The leader has as attribute the task of protecting his subordinates about the poor working conditions, the arbitrariness in the allocation of tasks and risks related to work, regardless of whether these conditions cause negative impacts on the efficiency of work. Thus, the quality of work and, in part, the quality of life, are functions of the leader. In this sense is that leadership must be conceived as a condition attribute or ability of a subject individual or collective mobilization of other subjects or individuals due to its action in situations of suffering, indecision or filling of wants and needs on the part of subordinates.